Infraestructura turística y afluencia de visitantes en el complejo “La Chorrera” en la Parroquia Balsapamba - Gaibor Olalla, Jhomaira Lisbeth (2019)
The case study called “infrastructure and influx of visitors at the La Chorrera tourist complex in Balsapamba parish, San Miguel canton, Bolívar Province, allowed us to assess the importance of tourist infrastructure in the attractiveness and the way in which it influences those who visit The case study shows that infrastructure allows tourism development worldwide. For this case study, information was collected, various methods were used, techniques that contributed and facilitated the collection of important or relevant data, together with surveys, conducted to the owner of the tourist complex "La Chorrera" and the main political authority of the parish . Improvements in the infrastructure of the Tourist Complex are recommended to encourage the influx of visitors, and the socio-economic development of Balsapamba Parish